ADAPTATION OF THE CAREER ADAPTABILITY SCALE (CAAS) MEASUREMENT TOOL FOR GENERATION Z JOB SEEKER IN YOGYAKARTA - Putu Eka Darmawan; Rosita Endang Kusmaryani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Study this aim for evaluate the adaptation and validation process tool measure the Indonesian version of the Career Adapt-Abilities Scale (CAAS) in context seeker Work Generation Z in Yogyakarta. Approach study use method quantitative with purposive sampling technique, involving 177 searchers Work Generation Z. Procedure adaptation follow Beaton et al.'s (2000) guidelines, which include forward translation, back translation, synthesis results translation, as well as expert review.​ Validity test construct done using Confirmatory Factor Analysis (CFA). The results show that model four CAAS dimensions, namely concern, control, curiosity, and confidence, meet goodness of fit criteria (CFI = 0.922; TLI = 0.912; RMSEA = 0.0733; SRMR = 0.0451). Total reliability of the scale reached 0.785, and each subscale show adequate internal consistency. Findings This indicates that the Indonesian version of CAAS is valid and reliable for used in context Indonesian culture, especially for those seeking Work Generation Z in Yogyakarta. Instruments This can used for measure adaptability career , as well as become base for study advanced related development career generation young people in Indonesia.